"Booze is the main factor that got me where I am today": alcohol use and HIV risk for MSM in rural South Africa. Issue 11 (2nd November 2018) - Daniels, Joseph; Struthers, Helen; Lane, Tim; Maleke, Kabelo; McIntyre, James; Coates, Tom
ABSTRACT: Excessive alcohol consumption has been shown to increase HIV risk for men who have sex with men (MSM) and compromise HIV prevention behaviors. However, there is limited contextual understanding of alcohol use for MSM in rural sub-Saharan African settings, which can inform and direct HIV interventions. Applying an adaptation of PhotoVoice, we worked with 35 HIV-positive MSM who created photo-essays about alcohol and HIV in Mpumalanga. A semi-structured protocol was used in focus group discussions that were audio-recorded, translated and transcribed. Transcript data and visual data of 24 photo-essays were analyzed using a constant comparison approach. We found that participants used alcohol to build and sustain social networks, meet sexual partners, and enhance sexual experience. Excessive alcohol use was common, which was associated with increased HIV risk behaviors within a community of MSM who maintained multiple partnerships. Our study suggests that HIV interventions need to address excessive alcohol use to mitigate the associated HIV risk at both the individual and community levels.